OPTIMALISASI OUTCOME ORGANISASI BERBASIS KEPEMIMPINAN SPIRITUAL - Wasitowati . (Jurnal Ekonomi dan Bisnis, 2011)
Spiritual leadership is an important factor in improving employee performance in government organizations. Some research has been done in order to optimize and create ongoing competitive advantage for organizations, however, more emphasis on aspects of non-human resources(tangible resources) and not much focus on the intangible resources of human capital. This study aims to determine Spiritual leaders in improving organizational outcomes. The sample in this study were employees of the District Court Office / Commercial / Corruption Semarang numbering as many as 153 people. Data obtained by conducting interviews equipped withinstruments questions. The question posed consisting of closed questions, where respondents choose the score of answer choices that are available as well as open questions. the spiritual leadership variables measured by seven indicators, four indicators of job satisfaction and performance of the five indicators. Everything is measured with a Likert scale of 1 -5. Analysisusing Partial Least Square (PLS).The results of data analysis by using the convergent validity showed that all indicator variables valid research (statistical T> T table) and a composite reliability values above 0.70. The results of hypothesis testing showed that spiritual leadership have a significant effect on satisfaction and performanceKeywords: spiritual leadership, job satisfaction, job performance